Isolation and Long-term Cultivation of Mouse Alveolar Macrophages - Busch, Clara Jana-Lui (Bio Protoc, 2019)
Alveolar macrophages (AM) are tissue-resident macrophages that colonize the lung around birth and can self-maintain long-term in an adult organism without contribution of monocytes. AM are located in the pulmonary alveoli and can be harvested by washing the lungs using the method of bronchoalveolar lavage (BAL). Here, we compared different conditions of BAL to obtain high yields of murine AM for in vitro culture and expansion of AM. In addition, we describe specific culture conditions, under which AM proliferate long-term in liquid culture in the presence of granulocyte-macrophage colony-stimulating factor. This method can be used to obtain large numbers of AM for in vivo transplantation or for in vitro experiments with primary mouse macrophages.